Strategi Komunikasi Korporasi Mixue dalam Upaya Membangun Citra Positif - Intan Purwi Maharani; Miftahus Saadah; Nanda Silvia Br Galingging; Riska Ferdiana (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This research aims to evaluate Mixue's corporate communication methods to create a positive perception of the wider audience. In this digital era, corporate image is one of the assets that affect the trust of customers. This research uses a qualitative approach based on critical analysis. The results show that the Mixue company uses several communication strategies, such as utilizing social media, open communication and transparency, cooperation with influencers, and using mascots as branding. These strategies help the brand's good reputation in the eyes of the public. It is hoped that this research will help develop corporate communication theory as well as provide practical examples of how a company builds and creates an image using good and effective strategies.